2019
DOI: 10.1249/mss.0000000000001964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Static Stretching and Foam Rolling on Ankle Dorsiflexion Range of Motion

Abstract: Static stretching (SS) has been used for inducing acute and long-term increases in range of motion (ROM). Foam rolling (FR) has recently gained popularity for acutely increasing ROM. However, the long-term effects of FR on ROM have not been thoroughly evaluated. Therefore, the purpose of this study was to investigate the acute and long-term changes in dorsiflexion ROM as a result of 6 wk of FR, SS, and FR followed by SS (FR + SS). Methods Participants (n = 44) were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 42 publications
5
29
0
Order By: Relevance
“…However, the vast majority of articles published since January 2018 confirm the pooled effects of FR, which are calculated in this meta-analysis. For example, Cheatham and Stull (2018), de Souza et al (2019), Hall and Chadwick Smith (2018), Killen et al (2018), Macgregor et al (2018), Madoni et al (2018), Monteiro et al (2018, 2019a,b), and Smith et al (2018, 2019) were able to confirm that FR can improve flexibility, perceived muscle pain perception, and/or the recovery of strength performance, while Madoni et al (2018) found that FR had no effect on jump performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the vast majority of articles published since January 2018 confirm the pooled effects of FR, which are calculated in this meta-analysis. For example, Cheatham and Stull (2018), de Souza et al (2019), Hall and Chadwick Smith (2018), Killen et al (2018), Macgregor et al (2018), Madoni et al (2018), Monteiro et al (2018, 2019a,b), and Smith et al (2018, 2019) were able to confirm that FR can improve flexibility, perceived muscle pain perception, and/or the recovery of strength performance, while Madoni et al (2018) found that FR had no effect on jump performance.…”
Section: Discussionmentioning
confidence: 99%
“…At each beep, the examiner foam moved the massager one stroke up or down. The intensity was steered based on the participants' feedback, targeting a 7/10 in discomfort on a numerical rating scale (0, no discomfort; 10, maximal discomfort) (Smith et al, 2019;Kiyono et al, 2020a). Based on previous studies, participants performed three sets of RM for 60 s with a 30-s break between sets (Smith et al, 2019;Behm et al, 2020;Kiyono et al, 2020a).…”
Section: Rm Interventionmentioning
confidence: 99%
“…Protocols usually involved 2-5 sessions per week delivered within a span of 3-8 weeks. The use of a ball or foam roller demonstrated its usefulness for improving shoulder, knee, or ankle ROM (Le Gal et al, 2018;Smith et al, 2019), without harmful consequences on physical performance (Hodgson et al, 2019). Regular combination of FR and static stretching may have an additional effect for increasing ROM (Mohr et al, 2014;Škarabot et al, 2015).…”
Section: Long-term Interventionsmentioning
confidence: 99%